Pathological study using ultrasound tests applied to structures under construction - Ergueta, Gustavo; Quino, Milton (Revista ALCONPAT, 2024)
The study discuss the results of the evaluation of reinforced concrete structures using non-destructive testing (NDT) based on ultrasonic pulse velocity (UPV) with the objective of determining the integrity and uniformity of the concrete, as well as detecting possible anomalies caused during construction or by external factors. The results showed the distribution of damage in a structure affected by fire, the measurement of cracking depth in a concrete element and the uniformity in different structural components, which subsequently allowed the development of the corresponding structural rehabilitation procedure. The study demonstrates the effectiveness of NDT and VPU in the evaluation of reinforced concrete structures, allowing immediate repair and rehabilitation decisions to be made.